2018
DOI: 10.1111/hsc.12585
|View full text |Cite
|
Sign up to set email alerts
|

Are veterans different? Understanding veterans’ help-seeking behaviour for alcohol problems

Abstract: Alcohol misuse in the United Kingdom's veteran community is not an isolated phenomenon. Internationally, alcohol and wider substance misuse would appear to be an historic and current global issue within veteran communities. Although research has been undertaken both in the United Kingdom and the United States into why veterans are reluctant to seek help for mental health problems, little is understood as to why veterans encounter difficulties in engaging with treatment for alcohol misuse. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Additionally, veterans discussed being on the receiving end of out‐group biases such as experiencing mental health stigmatization from other residents who sometimes viewed them as dangerous due to their mental illness, a common stigma veterans with PTSD face (Hipes & Gemoets, 2019). Overall, our findings align with previous research on veterans’ inability to relate to civilians or feeling misunderstood by them (Ahlin & Douds, 2016; Hinojosa & Hinojosa, 2011; Kiernan et al, 2018; Sayer et al, 2010). Results also highlight ways OH and other community settings can better support veterans by increasing mental health awareness and education for residents to reduce the stigma that veterans encounter.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, veterans discussed being on the receiving end of out‐group biases such as experiencing mental health stigmatization from other residents who sometimes viewed them as dangerous due to their mental illness, a common stigma veterans with PTSD face (Hipes & Gemoets, 2019). Overall, our findings align with previous research on veterans’ inability to relate to civilians or feeling misunderstood by them (Ahlin & Douds, 2016; Hinojosa & Hinojosa, 2011; Kiernan et al, 2018; Sayer et al, 2010). Results also highlight ways OH and other community settings can better support veterans by increasing mental health awareness and education for residents to reduce the stigma that veterans encounter.…”
Section: Discussionsupporting
confidence: 91%
“…A study of over 22 million Americans with current substance use disorders who had not sought care in the past year found the most commonly stated reasons were feeling unready to stop drinking and a lack of health insurance or means to pay for treatment (44). Lack of problem recognition and stigma are also common reasons for not seeking substance abuse treatment (8,45,46). A review of 17 population studies indicated that alcohol misuse is less likely to be perceived as a mental illness and is more stigmatized than other psychiatric disorders (47), which may account for the lower rate of treatment engagement across our sample for alcohol use disorder compared with PTSD and depression.…”
Section: Discussionmentioning
confidence: 91%
“…Complex presentations are common amongst veteran service users and findings from research concur that this is a typical presentation pattern [e.g. 11 13 25 41 ]. In the proposed ‘hub and spoke’ model, upon identification of a veteran, a multi-agency support worker would be assigned to the veteran to see them through accessing and engaging in the relevant services.…”
Section: Discussionmentioning
confidence: 99%
“…Participants cited key reasons for a lack of effective engagement of veterans in services including: a lack of understanding of veterans and the term ‘veteran’ itself, complexity of services, a normalisation of alcohol consumption and complex case presentations [e.g. 11 25 33 34 35 ]. In interviews with service planners, commissioners, and providers during phase one of the wider study; it was acknowledged that services have become more complex to navigate [ 11 ] and an acceptance that reluctance from competing services to work together was due to reduction in funding sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation